Historical pragmatics and early speech recordings: Diachronic developments in turn-taking and narrative structure in radio talk shows - Jucker, Andreas H.; Landert, Daniela (Journal of pragmatics, 2015)
In this study we analyse diachronic developments in some of the details of the turn-taking system (turn length, question intonation, hesitation markers) and the role they play in the narrative structures of conversations. Our investigation is based on audio recordings of a popular BBC Radio 4 talk show programme “Desert Island Discs”. These recordings have recently become available as a collection of podcasts reaching back to the 1950s. The early recordings are styled as interviews in a question - answer format. In more recent years, however, the presenter and the celebrity are more likely to cooperate in their different roles to jointly produce a narrative. The presenter brings in a larger amount of background knowledge on the details of the celebrity's life, which the audience may or may not share, and encourages the celebrity to pick up the narrative and continue the story. This overall change from an interview format to the format of a shared narrative is reflected in the minute details of the turn-taking system with differences in turn length and the use of question intonation and hesitation markers.